Brief moderate-intensity aerobic exercise improves the executive function of Chinese undergraduates regardless of mobile phone addiction: Evidence from the antisaccade task - Zhou, Junyi; Bai, Zhanshuang (Frontiers in Psychology, 2023)
Previous studies have shown that brief moderate-intensity aerobic exercise can improve the executive function of healthy adults. The present study sought to examine and compare the effects of brief moderate-intensity aerobic exercise on the executive functions of undergraduates with and without mobile phone addiction. Thirty-two healthy undergraduates with mobile phone addiction were recruited and randomly assigned to either an exercise or control group. Likewise, 32 healthy undergraduates without mobile phone addiction were recruited and randomly assigned to either an exercise or control group. Participants were asked to perform moderate-intensity aerobic exercise for 15 minutes for the exercise groups,. The executive functions of all participants were assessed via the antisaccade task twice (i.e., pre-test and post-test). The results showed that the saccade latency, variability of saccade latency, and error rate decreased significantly from pre-test to post-test for all participants. More importantly, after the 15-min moderate-intensity aerobic exercise intervention, participants in the exercise groups showed significantly shorter saccade latency than their counterparts in the control groups, regardless of whether they are with mobile phone addiction. This result is consistent with previous studies demonstrating that brief moderate-intensity aerobic exercise can improve one's executive function. Furthermore, the absence of significant interaction among Time, Group, and Intervention implies that the effects of brief moderate-intensity aerobic exercise on executive function are comparable between participants with and without mobile phone addiction. The present study supports the previous conclusion that brief moderate-intensity aerobic exercise can improve one's executive function effectively, and extends it to the population with mobile phone addiction. In summary, the present study has some implications for understanding of the relationship between exercise, executive function, and mobile phone addiction.